2021
DOI: 10.5435/jaaosglobal-d-21-00061
|View full text |Cite
|
Sign up to set email alerts
|

Do Medical Students Who Participate in a Research Gap Year Produce More Research During Residency?

Abstract: Background: The research gap year has become increasingly popular among medical students. It is also a well-known factor in consideration for orthopaedic surgery residency programs. Although medical students who participated in a research gap year typically enter residency with more research experience than their counterparts, it is unknown whether this translates to increased research productivity during residency compared with their peers. The purpose of this study was to investigate (1) whether r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Despite this, research activity remains one of the major variables considered by most orthopaedic training programs, both community and academic, in their evaluation of applicants [12,33]. Applicants with extensive research backgrounds are more heavily recruited with the hope and expectation that they will remain productive researchers in residency [39]. Research output directly affects faculty member promotion at academic institutions and potentiates their involvement in national orthopaedic societies.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, research activity remains one of the major variables considered by most orthopaedic training programs, both community and academic, in their evaluation of applicants [12,33]. Applicants with extensive research backgrounds are more heavily recruited with the hope and expectation that they will remain productive researchers in residency [39]. Research output directly affects faculty member promotion at academic institutions and potentiates their involvement in national orthopaedic societies.…”
Section: Limitationsmentioning
confidence: 99%
“…Although research is not a primary focus for many residents, research productivity was included as a criterion because research activity is a major variable considered by most orthopaedic training programs in their evaluation of applicants [12,20,33]. Both residency and fellowship programs hope that their applicants will be productive researchers while training and thus typically recruit applicants with extensive research backgrounds more heavily [5,28,39]. Finally, personality was included as a parameter because a sizeable body of literature from over a dozen centers exists with the goal of identifying personality traits such as grit, selfcontrol, and conscientiousness [3,15,18,19,34].…”
Section: Faculty Assessment Of Graduated Residentsmentioning
confidence: 99%
“…Cruz et al defined academic productivity based upon faculty status and academic productivity score, a combination of various achievements and activities that are important for a successful academic career, such as postresidency research publications, faculty status, grants, editorial board membership, reviewer appointment, and mentorship. This study, like others, defined academic productivity based on the number of PubMed indexed PRPs, as this provides an objective quantitative score and is an academic standard …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Wright-Chisem et al and Kohlert et al examined publication rates before and during orthopaedic and otolaryngology residency, respectively. 27 , 28 The authors found that applicants who publish research before residency are significantly more likely to continue publishing during residency (Wright-Chisem et al; P < 0.001, Kohlert et al; P < 0.001). In addition, Wright-Chisem et al 27 found that residents who completed a gap year research fellowship produced significantly more peer-reviewed publications than those who did not complete a research fellowship ( P = 0.025).…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 The authors found that applicants who publish research before residency are significantly more likely to continue publishing during residency (Wright-Chisem et al; P < 0.001, Kohlert et al; P < 0.001). In addition, Wright-Chisem et al 27 found that residents who completed a gap year research fellowship produced significantly more peer-reviewed publications than those who did not complete a research fellowship ( P = 0.025). These studies demonstrate the lasting effect a research fellowship can have once an applicant matches into residency.…”
Section: Discussionmentioning
confidence: 99%